2012
DOI: 10.1016/s0027-9684(15)30137-1
|View full text |Cite
|
Sign up to set email alerts
|

The Females Against Cancer Educational Series: A Qualitative Evaluation of Mother/Daughter Knowledge and Perceptions of Human Papillomavirus and Its Related Cancers

Abstract: Objective To evaluate the knowledge, perceptions, and effectiveness of an human papillomavirus (HPV)/cervical cancer education/prevention program. Methods Approximately 50 middle and high school girls and their mothers participated in the 7-part educational series. Qualitative pre-evaluations and postevaluations were completed for every session, followed by culminating focus groups with mothers and daughters separately. Results Common themes included lack of basic knowledge about HPV and its related cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Askelson et al (2010), Jeudin et al (2014), Kepka et al (2012), and Ramirez, Jessop, Leader, and Crespo (2014) all found that mothers tend to refuse HPV vaccination for their daughters due to concerns about vaccine safety, fears of promoting promiscuity, and the belief that vaccination was unnecessary if their daughter was not engaging in sexual activity. Louis-Nance et al (2012) found that poor mother–daughter communication about sexuality and sexual health led mothers to be against HPV vaccination for their daughters. Mothers are frequently influenced by their husbands' perspectives, and many men oppose HPV vaccination due to fears that their daughters will engage in promiscuous behaviors (Kepka et al, 2012; Schmidt-Grimminger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Askelson et al (2010), Jeudin et al (2014), Kepka et al (2012), and Ramirez, Jessop, Leader, and Crespo (2014) all found that mothers tend to refuse HPV vaccination for their daughters due to concerns about vaccine safety, fears of promoting promiscuity, and the belief that vaccination was unnecessary if their daughter was not engaging in sexual activity. Louis-Nance et al (2012) found that poor mother–daughter communication about sexuality and sexual health led mothers to be against HPV vaccination for their daughters. Mothers are frequently influenced by their husbands' perspectives, and many men oppose HPV vaccination due to fears that their daughters will engage in promiscuous behaviors (Kepka et al, 2012; Schmidt-Grimminger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Parents’ awareness of HPV and vaccination has increased (Matthews & Matsumoto, 2014); more know about the severity of HPV, how common it is, how the infection is transmitted, the availability of a vaccine to prevent exposure to cervical cancer, and the recommended age group for vaccination (Allen et al, 2010; Chow et al, 2010; Guerry et al, 2011; Kepka, Ulrich, & Coronado, 2012). However, simply being aware of HPV does not mean parents are knowledgeable (Allen et al, 2010; Louis-Nance et al, 2012; Schmidt-Grimminger et al, 2013), which is defined by their understanding of HPV transmission, the type of cancers it causes, who is affected, diagnostic testing for it, associated risk factors, recommended age for vaccination, purpose of the vaccine, which strains vaccination prevents, and the number of injections required (Kepka, Coronado, Rodriguez, & Thompson, 2011; Kepka et al, 2012; Kornfeld, Byrne, Vanderpool, Shin, & Kobetz, 2013; Louis-Nance et al, 2012; Okoronkwo, Sieswerda, Cooper, Binette, & Todd, 2012). HPV awareness and knowledge are strongly associated with using the vaccine (Allen et al, 2010; Guerry et al, 2011; Hendry, Lewis, Clements, Damery, & Wilkinson, 2013; Okoronkwo et al, 2012).…”
mentioning
confidence: 99%
“…Three of the 33 studies designed culturally appropriate interventions tailored to a vulnerable or understudied population (Kerr et al, 2013; Loescher et al, 2019; Louis-Nance et al, 2012). Kerr et al (2013) created an intervention tailored to African American adolescents in four U.S. cities that “invok[ed] positive cultural characteristics that reflect the African American experience.” Louis-Nance et al (2012) prioritized African American adolescents in response to HPV racial disparities. Loescher et al (2019) worked with community partners to adapt a sun safety program to Latinx adolescents in response to the increasing rate of skin cancer and lack of education research in Latinx populations.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, even HPV education, which often focuses on cervical cancer and targets females, could be more inclusive and move beyond gender-specific education. Louis-Nance et al (2012) addressed HPV-related cancers beyond cervical cancer but was limited to female adolescents. Among HPV-attributable cancers (cervical, vagina, vulva, penis, anus, and oropharynx), the number of oropharynx cancers now exceeds estimates of cervical cancers attributable to HPV (Saraiya et al, 2015).…”
Section: Cancer Types and Risk Factorsmentioning
confidence: 99%
“…Für Impffragestellungen haben sich Fokusgruppen als Methode bewährt, z. B. bei der Impfung gegen humane Papillomviren (HPV) [17,18].…”
Section: Hintergrundunclassified